Ownership structure and sustainable firm performance: a literature review - Mehreen, Mehreen; Hassan, Rusni; Sayal, Azizullah (Foundation University Islamabad (FUI), Pakistan, 2024)
Purpose: This study aims to explore the contemporary issues in ownership structure towards the sustainable firm’s performance for strategic managerial policy. Design/methodology/approach: This study followed the systematic literature review technique. Findings: Results found that most of the prior literature on this subject is related to developed countries, while research on this subject in developing countries is found scant. Originality: This study offers new propositions on contemporary issues in ownership structure. The proposition alludes to a significant positive impact of managerial ownership, institutional ownership, and family ownership toward achieving sustainable firm performance. Research limitations/implications: This review offers insights to managers and practitioners from developing countries towards maintaining a balance between the ownership of various stakeholders towards achieving a better and sustainable firm performance.